A new species of Aspidosperma (Apocynaceae) from the Brazilian Cerrado - Scudeler, Ana Laura; Devides Castello, Ana Carolina; de Souza Pereira, Andreza Stephanie; Koch, Ingrid (Phytotaxa, 2018)
Aspidosperma rizzoanum is a new species of Cerrado from Goiás and Tocantins states, Brazil. Here we provide the description and illustration of this new species and, besides that, a comparative table and an identification key to the species occurring in the Cerrado of Goiás and Tocatins.